2003
DOI: 10.1177/104063870301500204
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Reproduction of Postweaning Multisystemic Wasting Syndrome in Cesarean-Derived, Colostrum-Deprived Piglets Inoculated with Porcine Circovirus Type 2 (PCV2): Investigation of Quantitative PCV2 Distribution and Antibody Responses

Abstract: Abstract. Sixteen cesarean-derived, colostrum-deprived piglets were inoculated intranasally with porcine circovirus type 2 (PCV2), originally isolated from a pig affected with postweaning multisystemic wasting syndrome (PMWS). At 1 day postinoculation (PI), 3 of the 5 piglets in the uninoculated control group were moved to the room of inoculated piglets for contact exposure. Porcine circovirus type 2 was detected by polymerase chain reaction (PCR) in swabs from inoculated piglets from 1 day PI and from contact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
48
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(49 citation statements)
references
References 29 publications
1
48
0
Order By: Relevance
“…In previous studies, coinfections with other porcine viruses or immunostimulation have been shown to be important in the development of clinical PMWS [1,7,8]. In contrast, a recent report demonstrated that PCV-2 could induce clinical PMWS in piglets in the absence of other swine pathogens [10]. In the case presented here, the inoculum of tissue homogenates was shown to be free from PCV-1, PPV and PRRSV.…”
mentioning
confidence: 53%
“…In previous studies, coinfections with other porcine viruses or immunostimulation have been shown to be important in the development of clinical PMWS [1,7,8]. In contrast, a recent report demonstrated that PCV-2 could induce clinical PMWS in piglets in the absence of other swine pathogens [10]. In the case presented here, the inoculum of tissue homogenates was shown to be free from PCV-1, PPV and PRRSV.…”
mentioning
confidence: 53%
“…In this study, we observed this outcome in only one GF animal that was inoculated with the PCV2 688 isolate (Additional file 2) while other investigators report 40% mortality in SPF animals [17] and~50% of conventional animals [18]. The extent of PCV2 viremia may also differ among GF piglets [8], colostrum-deprived piglets [16], and conventional pigs [1]. Clinical PMWS, unlike SIV and PRRSV, is often late to develop and occurs beyond the 5-6 weeks in which GF piglets can be maintained in isolators.…”
Section: Cd8αmentioning
confidence: 46%
“…However, the response of T cells is generally weak [21]. Although the appearance of specific antibodies is delayed [16,21], subclinical PCV2 infection is characterized by the presence of neutralizing antibodies that correlate with protection from PCV2 infection [20].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations